Improvement on pull-in thrust to input power of HDTFLM using optimal chopping strategy - Zare, Mohsen R.; Misron, Norhisam; Aravind, C. V.; Raja Othman, Raja Nor Firdaus Kashfi; Aris, Ishak; Mariun, Norman; Wakiwaka, Hiroyuki (2013)
An optimal chopping strategy to enhance the ratio of pull-in thrust to input power for the high density transverse flux linear motor is presented. The high density transverse flux linear motor is a novel machine combining the characteristics of the high density linear motor and the transverse flux linear machines. The analytical approach presents that if the ratio of the pull-in thrust to the input power is made higher, then the machine performance can be improvised to a greater extent. In this investigation the single pulse given to the drive element is modulated for the reduction in the power consumption. Experimentation is performed under different load condition until the motor come to the standstill value. The results show that the utilization of the optimal chopping strategy improvised the ratio of pull-in thrust to power consumed during the start time by 5.5% higher value while the input power consumed is reduced by 19.82%. The efficiency of motor under the optimal chopping mode is 5.52% higher than that using the nominal applied voltage.